P-28 The art of dying well. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Doherty, Margaret
Abstract : The Catholic Church in England and Wales has brought the medieval manuscript Ars Moriendi – The Art of Dying – into the digital age, with a website -www.artofdyingwell.org – aimed at helping terminally ill people and their loved ones deal with death. Like the original 15th century work, The Art of Dying Well is intended to bring spiritual comfort and to offer practical guidance to people in the final stage of life. The modern – day version offers videos, animations and interviews with terminally ill people and their carers. Who is it for?: People who are dying People with a friend or relative who is dying/has died People who care for the dying in a professional context People who are surviving death, or battling a life – threatening disease The national conversation around death: As well as developing the Art of Dying Well website and engaging in the digital conversation around death, the Art of Dying Well initiative is taking part in the national conversation around death and helping to raise 'literacy levels' on the topic of dying well and appreciation of spiritual care in the process. To date, the Art of Dying Well has and continues to receive significant coverage in the Guardian, Times, LBC radio, BBC News, BBC Five Live, BBC Radio 2, Vatican Radio, and the Catholic press. What People Say: 'It speaks powerfully into this awkward, immature silence around death. And I believe it has the potential to alleviate much suffering. I've seen it used with clinicians, families and patients. And I have seen it be a powerful help.' Dr Jim McManus, Director of Public Health, Hertfordshire County Council.